Syngas/power cogeneration from proton conducting solid oxide fuel cells assisted by dry methane reforming: A thermal-electrochemical modelling study. (1st July 2018) - Chen, Bin; Xu, Haoran; Sun, Qiong; Zhang, Houcheng; Tan, Peng; Cai, Weizi; He, Wei; Ni, Meng
Graphical abstract: Highlights: A novel syngas/electricity co-generator based on solid oxide fuel cell is designed. High conversion of CH4 (82.5%) and CO2 (83%) to syngas and power are achieved. H2 electrochemical oxidation could enhance the methane dry reforming process. Effects of operating voltage and inlet flow rate are investigated. Abstract: A tubular proton conducting solid oxide fuel cell (H-SOFC) integrated with internal dry methane reforming (DMR) layer is numerically studied for power and syngas cogeneration using CO2 and CH4 as fuel by the Finite Element Method. The coupled heat and mass transporting with electrochemical reactions and chemical reactions (DMR, water gas shifting reaction and methane steam reforming) are fully considered. The model is substantially validated with experimental data of DMR catalyst characterization and SOFC button cell electrochemical characterization. The base case analyses are conducted at open circuit voltage (OCV) and 0.7 V of the DMR-SOFC. It is found that the CO2 conversion and CH4 conversion can be increased by 4.8% and 21.6%, respectively, by increasing the operating voltage of DMR-SOFC from OCV to 0.7 V, with the coproduction of electricity (1.5 W). These conversion enhancements were caused by the in-situ integration of the endothermal DMR reaction and exothermal H2 electrochemical oxidation. Effects of operating voltage and inlet flow rate of feeding gas are evaluated. The voltage is suggested to be higher than 0.5 V to avoid large temperature gradient in the reactor. It is also found that conversion ratios of both CH4 and CO2 decrease from over 90% to be below 60% as the fuel flow rate is increased from 40 cm 3  min −1 to 80 cm 3  min −1 .